Generalized Stages in the Development of Labor and Human Participation in the Economy - Pirimova, Vera; Pirimova, Elka (Research Papers, 2023)
In the study, a classification of larger stages was carried out, within which more significant changes (transformations) occur in the character, the dominant types of labor and the role of human participation in production and the economy. For this purpose, a complex criterion was compiled and applied, according to which five generalized stages in the development of labor in a historical perspective are distinguished. Transformations in labor at each stage are specified and tied to accompanying significant changes in the entire system of production factors, in the prevailing type and sectoral structure of the economy. Generally accepted methods and approaches are applied in the research, including the historical and logical approach, the principles and means of economic analysis and synthesis, the deductive and inductive method, the comparative analysis.